Expel Riba with Islamic Transactions (Analysis of Islamic Financial Institutions) - Saharuddin, Desmadi; Meirison, Meirison (Universitas Islam Negeri Raden Fatah Palembang, 2022)
This article aims to explain the importance of the steps that Islamic banks must take to stay away from usury to increase Muslim confidence in Islamic banking, which has been stretched all this time to revive the Muslim economy. Riba can cause prolonged inflation and even make the country's economy collapse slowly. However, there are still many usury practices carried out by Islamic banks due to several factors, such as central bank regulations and managers who do not yet understand the rules of Islamic law. This discussion is carried out through a literature study and a descriptive analysis approach through documents and journals that discuss Islamic banking. We interpret the results obtained: Islamic banking is still involved in Mu'amalah Riba, which is more than an extension of conventional banks that sell their products. However, there is still an event to get away from usury by implementing the rules of Islamic Shari'ah thoroughly by developing the proper investment methods. Islamic banks may perform Mudharabah (profit sharing), Musyarakah, Murabahah, Ijarah, and Muzara'ah by paying attention to the distribution of profits and losses by Islamic law. Let these trading and investment instruments be carried out in real terms with full responsibility.